Label-free 1D microfluidic dipstick counting of microbial colonies and bacteriophage plaques. Issue 15 (6th July 2022) - Dönmez, Sultan İlayda; Needs, Sarah H.; Osborn, Helen M. I.; Reis, Nuno M.; Edwards, Alexander D.
Abstract : Miniaturised 1D liquid colony and plaque counting method. Counting viable bacterial cells and functional bacteriophage is fundamental to microbiology underpinning research, surveillance, biopharmaceuticals and diagnostics. Abstract : Counting viable bacterial cells and functional bacteriophage is fundamental to microbiology underpinning research, surveillance, biopharmaceuticals and diagnostics. Colony forming unit (CFU) and plaque forming unit (PFU) counting still requires slow and laborious solid culture on agar in Petri dishes or plates. Here, we show that dip-stick microfluidic strips can be used without growth indicator dye for rapid and simple CFU ml −1 and PFU ml −1 measurement. We demonstrate for the first time that fluoropolymer microcapillaries combined with digital imaging allow bacteriophage plaques to be counted rapidly in a dip-and-test format. The microfluidic length scales offer a linear 1-dimensional alternative to a 2D solid agar medium surface, with colonies or plaques clearly visible as "dashes" or "gaps". An inexpensive open source darkfield biosensor system using Raspberry Pi imaging permits label-free detection and counting of colonies or plaques within 4–8 hours in a linear, liquid matrix within ∼200 μm inner diameter microcapillaries. We obtained full quantitative agreement between 1D microfluidic colony counting in dipsticks versus conventional 2D solid agar Petri dish plates for S. aureus and E. coli, and for T2 phage and phage K, but up to 6 times faster. Time-lapse darkfield imaging permitted detailed kinetic analysis of colony growth in the microcapillaries, providing new insight into microfluidic microbiology and colony growth, not possible with Petri dishes. Surprisingly, whilst E. coli colonies appeared earlier, subsequent colony expansion was faster along the microcapillaries for S. aureus . This may be explained by the microenvironment offered for 1D colony growth within microcapillaries, linked to a mass balance between nutrient (glucose) diffusion and bacterial growth kinetics. Counting individual colonies in liquid medium was not possible for motile strains that spread rapidly along the capillary, however inclusion of soft agar inhibited spreading, making this new simple dip-and-test counting method applicable to both motile and non-motile bacteria. Label-free dipstick colony and plaque counting has potential for many analytical microbial tasks, and the innovation of 1D colony counting has relevance to other microfluidic microbiology.